Unilateral tariff reduction as leadership in the political economy of trade negotiations - Daniel E. Coates; Rodney D. Ludema (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1995)
This paper develops a model of the trade liberalization process, featuring both international negotiation and special-interest-driven domestic politics. We show that a country may wish to adopt a policy of unilaterally reducing its tariff whenever political opposition in other countries stalls negotiations toward free trade, because such a policy weakens the political opposition in those countries and expedites the liberalization process. Thus a pattern emerges in which unilateral liberalization by one large country (the leader) is followed by a greater likelihood of trade reform in other countries, with deeper tariff cuts therein. Moreover, we show that this pattern may be more pronounced the larger is the leader country. These results help to explain the cases of mid-nineteenth-century Britain and mid-twentieth-century United States and to support a theory of international leadership in trade policy-making.
Keywords: 330; Handelsliberalisierung; Zollpolitik; Verhandlungen; Neue politische Ökonomie; Theorie